Investigating the Effectiveness of Different Porous Nanoparticles as Drug Carriers for Retaining the Photostability of Pinosylvin Derivative - Howaili, Fadak (MDPI, 2025)
Pinosylvin monomethyl ether (PsMME) is a natural compound known for its valuable bioactive properties, including antioxidant and anti-inflammatory effects. However, PsMME's susceptibility to photodegradation upon exposure to ultraviolet (UV) radiation poses a significant limitation to its applications in the pharmaceutical field. This study, for the first time, introduces a strategy to enhance the photostability of PsMME by employing various nanoformulations. We utilized mesoporous silica nanoparticles (MSNs) coated with polydopamine via a poly(ethylene imine) layer (PDA-PEI-MSNs), thermally carbonized porous silicon nanoparticles (TCPSi), and pure mesoporous polydopamine nanoparticles (MPDA). All these nanocarriers exhibit unique characteristics, including the potential for shielding the drug from UV light, which makes them promising for enhancing the photostability of loaded drugs. Here, these three nanoparticles were synthesized and their morphological and physicochemical properties, including size and zeta-potential, were characterized. They were subsequently loaded with PsMME, and the release profiles and kinetics of all three nanoformulations were determined. To assess their photoprotection ability, we employed gas chromatography with a flame ionization detector (GC-FID) and gas chromatography-mass spectrometry (GC-MS) to assess the recovery percentage of loaded PsMME before and after UV exposure for each nanoformulation. Our findings reveal that MPDA exhibits the highest protection ability, with a remarkable 90% protection against UV light on average. This positions MPDA as an ideal carrier for PsMME, and by extension, potentially for other photolabile drugs as well. As a final confirmation of its suitability as a drug nanocarrier, we conducted cytotoxicity evaluations of PsMME-loaded MPDA, demonstrating dose-dependent drug toxicity for this formulation.